The Application Of PCR (Polymerase Chain Reaction) Using Specific Primer To Detect Chillies Drought Tolerant: Aplikasi PCR (Polimerase Chain Reaction) Menggunakan Primer Spesifik Untuk Mendeteksi Cabai yang Toleran Terhadap Kekeringan - Ria Oktavianti (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2019)
The purpose of this study was to find tolerant genotypes. This research was conducted on 16 chilli genotypes from UIN Suska Riau Laboratory of Breeding and Genetics. Using four specific primers wich were TIL, DREB2A, P5CS, and Primary Pair 2 (BLAS). Results of the study showed amplifikasi of chilli DNA could be obtained using TIL and Pair 2. Primer however th corsponding result were obtain only by using TI to be drought tolerant, while 5 genotypes were found drought intolerant. The drought tolerant genotypes were (RFC-005), (RFC-006), (G-UIN- 016), (G-UIN-015), (G-UIN-065), (UIN-097), (UIN-035), (UIN-100), (UIN-099), (UIN-037) and (UIN-096). While 5 intolerant genotypes were (G-UIN-019), (G-UIN-008), (G-UIN-038), (RFC-013) and (UIN-036).